1983
DOI: 10.1128/iai.42.1.427-430.1983
|View full text |Cite
|
Sign up to set email alerts
|

Evidence indicating that the cholera toxin structural genes of Vibrio cholerae RJ1 and 3083-2 are between met and trp

Abstract: An enterotoxin A subunit-specific radioactive probe was used to correlate expression of vct-1 or vct-2 with the presence of specific restriction fragments in the DNAs of several wild-type and recombinant Vibrio cholerae strains. The data are consistent with the conclusion that vct is a cholera toxin structural gene. We previously reported that the gene vct specifies the antigenic structure of cholera toxin (CT) and is located between met and trp on the Vibrio cholerae genetic map (14). The vet-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In contrast, all classical biotype strains showed hybridization of probe 1 to two PstI or XbaI fragments. Except for strains RJ57 and RJ57(RP4), these results are in agreement with published reports and confirm that the CT operon is present at two locations in classical strains and at one location on the chromosome of most El Tor strains (12,14,16,19,24,25). The third PstI and XbaI fragments observed in our experiments with DNA from strains RJ57 and RJ57(RP4), which are derived from El Tor strain RV79 (10), presumably hybridized with the flanking sequences of probe 1 and not with CT operon-specific sequences (16).…”
supporting
confidence: 92%
“…In contrast, all classical biotype strains showed hybridization of probe 1 to two PstI or XbaI fragments. Except for strains RJ57 and RJ57(RP4), these results are in agreement with published reports and confirm that the CT operon is present at two locations in classical strains and at one location on the chromosome of most El Tor strains (12,14,16,19,24,25). The third PstI and XbaI fragments observed in our experiments with DNA from strains RJ57 and RJ57(RP4), which are derived from El Tor strain RV79 (10), presumably hybridized with the flanking sequences of probe 1 and not with CT operon-specific sequences (16).…”
supporting
confidence: 92%
“…Wild-type El Tor strain RJ1 and recombinants with tox-1000 are designated Tox-because these strains do not produce quantities of CT that can be detected in the Elek test or the radial passive immune hemolysis assay for CT, whereas wild-type El Tor strain 3083-2 and recombinants with tox-2000 are toxinogenic in these tests. Genetic mapping experiments indicated that tox-1000 is separated from the CT structural genes of strain RJ1 by at least one gene that is not related to CT synthesis (trp), implying that tox-1000 transregulates the CT structural genes (14)(15)(16). Miller and Mekalanos (12) and Sporecke et al (17) subsequently provided evidence supporting a similar conclusion for the CT regulatory and structural genes of strain 569B.…”
mentioning
confidence: 87%
“…Two observations suggest that it is most likely that the 12-and 2.4-kb nuclease restriction fragments were derived from pSJ13, the plasmid that was used to mobilize the donor chromosome. First, we previously reported that 32P-nick-translated pBR322 DNA hybridizes with a 2.4-kb PstI nuclease restriction fragment in RJ1(pSJ13) whole cellular DNA but not in RJ1 whole cellular DNA (14). We suggested that the P-lactamase gene of pBR322 hybridized to the 3-lactamase gene of pSJ13.…”
mentioning
confidence: 99%
See 2 more Smart Citations